O modyelyakh 2D N=1 i 4D N=2 tyeorii Yanga-Millsa na ryeshyetkye - Aratyn, H.; Goto, M.; Zimerman, A. H. (Springer Nature, 1985)
Supersymmetric interacting models, like the two-dimensional N=1 Wess-Zumino model and N=2 Yang-Mills theory, are constructed on the space lattice. The Becher-Joos techniques, for the Dirac-Kähler formulation on the lattice, are extensively used in order to obtain the supercurrents and Hamiltonians on the lattice, even in the interacting case. We show that it is possible to construct the invariant actions for these models with the correct classical continuum limit. Our work is based on the new method of putting the fields in the adjoint representations on the lattice. © 1985 Società Italiana di Fisica.
Keywords: Field theory